2021
DOI: 10.1556/2006.2021.00084
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive sexual behavior, religiosity, and spirituality: A systematic review

Abstract: Background and aims In recent years, increasing attention has been given to the relationship between compulsive sexual behavior (CSB), religiosity, and spirituality. This review summarizes research examining the relationship CSB has with religiosity and spirituality, clarifying how these constructs inform the assessment and treatment of this syndrome. Methods The present paper reviews research published through August 1, 2021, using the Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Criticism has been specifically raised against the application of the addiction model to the out-of-control use of the internet for sexual purposes, which has been deemed inappropriate due to a lack of evidence for the presence of all six addiction-model components ( 26 , 28 , 29 ). Moreover, a large number of studies [see ( 30 , 31 ) for systematic review] found that religiosity or moral incongruence may affect the perceptions of one's own behavior and ultimately lead to the overestimation of the problem and an inappropriate (self) diagnosis. On the other hand, Gola et al ( 32 ) stated that moral incongruence (i.e., the potential religiosity behind it) is culturally influenced and its status as exclusion criteria for PSIU is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Criticism has been specifically raised against the application of the addiction model to the out-of-control use of the internet for sexual purposes, which has been deemed inappropriate due to a lack of evidence for the presence of all six addiction-model components ( 26 , 28 , 29 ). Moreover, a large number of studies [see ( 30 , 31 ) for systematic review] found that religiosity or moral incongruence may affect the perceptions of one's own behavior and ultimately lead to the overestimation of the problem and an inappropriate (self) diagnosis. On the other hand, Gola et al ( 32 ) stated that moral incongruence (i.e., the potential religiosity behind it) is culturally influenced and its status as exclusion criteria for PSIU is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…As with any study, this study had limitations. The sample suffers from the same problem of low ethnic and sexual orientation diversity as studies of sexual compulsivity (Jennings et al, 2021). However, this might reflect the nature of these particular men, many following a program with forums commonly assailing LGBT persons.…”
Section: Discussionmentioning
confidence: 99%
“…All items were phrased with gender-equitable and -sensitive language [ 21 ]. The questionnaire was divided into four parts.…”
Section: Methodsmentioning
confidence: 99%
“…Positive correlations were found between HB and neuroticism [16,17], hostility [16], sensation seeking [16,18], impulsivity [18,19], loneliness and lower levels of satisfaction with life and happiness [15,20]. Also, a relation between religiosity and HB is suggested, possibly explained by moral incongruence and feelings of shame and guilt regarding the individual sexual behaviour of the affected persons [21,22]. HB occurs often simultaneously with other psychiatric diseases and is associated with the adherence of them (e.g.…”
Section: Introductionmentioning
confidence: 99%